Telehealth and Telemedicine in Health Service Presentation: TELEHEALTH AND TELEMEDİCİNE (Turkey Health Literacy Journal, 2022)
Telemedicine (telehealth) applications have become mainstream in many areas of health care and are accepted as the preferred service delivery method that increases access to health services.Today, telemedicine applications; to provide health services to people with more limited access to health, to increase the use of telemedicine applications not only in acute cases but also in chronic and periodic diseases, to enable health workers to access telemedicine applications not only from the hospital but also from anywhere, to encourage health workers to use telemedicine applications, to encourage healthcare professionals to use telemedicine applications, There is a tendency to increase depending on reasons such as increasing the number of working hours.In the study, it was aimed to evaluate the initial process of the project in primary health care services provided in Altındağ, Çankaya, Gölbaşı, Sincan and Yenimahalle districts of Ankara province, which were included in the “Distance Health Service Delivery (Telemedicine) Project” initiated in Ankara, Samsun and Konya provinces.In order to increase the frequency of use of telemedicine applications especially in chronic disease management, to encourage healthcare professionals to use telemedicine applications, and to eliminate the problems experienced in practice, face-to-face and online training was provided to 194 healthcare professionals. Healthcare professionals are called periodically by phone to receive their feedback, provide information and correct any problems experienced.When telemedicine applications are evaluated together with the pandemic experiences, it is certain that it will be beneficial not only in the delivery of treatment services, but also in the protection and development of health, health education and health surveillance. In this way, it will contribute to the reduction of the disease burden and health expenditures, and thus to the country’s economy.